2021
DOI: 10.3390/ijerph18010311
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Street-View Greenery on Fear of Neighborhood Crime in Guangzhou, China

Abstract: Previous literature has examined the relationship between the amount of green space and perceived safety in urban areas, but little is known about the effect of street-view neighborhood greenery on perceived neighborhood safety. Using a deep learning approach, we derived greenery from a massive set of street view images in central Guangzhou. We further tested the relationships and mechanisms between street-view greenery and fear of crime in the neighborhood. Results demonstrated that a higher level of neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 62 publications
(72 reference statements)
0
9
1
Order By: Relevance
“…Both models suggest that violent crimes tend to occur more often in more populated block groups with lower median household incomes, higher concentrations of ethnic minorities, harmful product sales outlets, and dilapidated neighborhood environments. This result is not different from many of the previous studies’ findings [ 2 , 7 , 14 , 15 , 24 , 35 , 90 , 91 , 92 ]. The result is also one of the cornerstones for municipal governance and policing practices.…”
Section: Discussioncontrasting
confidence: 60%
“…Both models suggest that violent crimes tend to occur more often in more populated block groups with lower median household incomes, higher concentrations of ethnic minorities, harmful product sales outlets, and dilapidated neighborhood environments. This result is not different from many of the previous studies’ findings [ 2 , 7 , 14 , 15 , 24 , 35 , 90 , 91 , 92 ]. The result is also one of the cornerstones for municipal governance and policing practices.…”
Section: Discussioncontrasting
confidence: 60%
“…Recently, Yi et al (2019) and Yiyong et al (2020) uncovered the inconsistency by proving that eye-level greenness extracted from street view image data with deep learning methods was positively associated with cycling activities and dockless bike-sharing usage, respectively, rather than overhead view greenness measured by the normalized difference vegetation index (NDVI). Additionally, some studies have shown that eye-level greenness might better measure greenness out of cyclists' subjective feelings and sights than overhead view greenness [3][4][5]30,[35][36][37][38]. Hence, street view image data and deep learning segmentation methods have become efficient data sources and assessment methods for measuring urban greenness, which has been applied in transport geography, psychology, and crime studies [3,35,37,38].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, some studies have shown that eye-level greenness might better measure greenness out of cyclists' subjective feelings and sights than overhead view greenness [3][4][5]30,[35][36][37][38]. Hence, street view image data and deep learning segmentation methods have become efficient data sources and assessment methods for measuring urban greenness, which has been applied in transport geography, psychology, and crime studies [3,35,37,38].…”
Section: Related Workmentioning
confidence: 99%
“…Green elements such as trees and grass can facilitate people’s outdoor activities and thus promote informal monitoring, thereby restraining the occurrence of crimes. However, thick shrubs may obstruct people’s lines of sight and provide hiding places for offenders; therefore, areas with shrubs have potential crime risks [ 1 , 23 , 24 , 25 ]. A holistic investigation of these features and their possible interactions remains unanswered.…”
Section: Introductionmentioning
confidence: 99%